The Influence of Rational Content Marketing and Brand Image on PYARY Consumer Loyalty: Pengaruh Rational Content Marketing dan Citra Merek terhadap Loyalitas Konsumen PYARY - Aurelia; Desma Erica Maryati Manik (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to analyze the influence of Rational Content Marketing and Brand Image on Consumer Loyalty of PYARY soap products in Medan City. The research method used is quantitative by distributing questionnaires to 219 respondents, and data processing using validity tests, reliability, multiple linear regression analysis, t test, F test, and coefficient of determination. The results of the study indicate that Rational Content Marketing partially has no positive and significant effect on Consumer Loyalty, with a calculated t value of 0.475 <ttable 1.652 and a significance of 0.635> 0.05. On the other hand, Brand Image has a positive and significant effect with a calculated t value of 4.865> ttable 1.652 and a significance of 0.000 <0.05. Simultaneously, both variables have a significant effect on Consumer Loyalty with a calculated F value of 79.597> Ftable 3.04 and a significance value of 0.000 <0.05. The coefficient of determination (R²) of 0.424 shows that 42.4% of the variation in Consumer Loyalty is influenced by Rational Content Marketing and Brand Image, while 57.6% is influenced by other factors outside the research.